(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Eventhough Abbas output is meager in terms of his writing in view of his slendervolume of “Inquilab” “The world is my village” and the auto biography “I am notan Island”, we have to rank him as a supreme short story writer for his richand abundant contribution to the distinct genre of short story, his novella“The walls of glass” nearly a hundred short stories merit the attention of anavid reader as well as an erudite scholar.